Analysis of the t(3;8) of Hereditary Renal Cell Carcinoma: A Palindrome-Mediated Translocation - Kato, Takema (2014)
It has emerged that palindrome-mediated genomic instability generates DNA-based rearrangements. The presence of palindromic AT-rich repeats (PATRRs) at the translocation breakpoints suggested a palindrome-mediated mechanism in the generation of several recurrent constitutional rearrangements: the t(11;22), t(17;22) and t(8;22). To date, all reported PATRR mediated translocations include the PATRR on chromosome 22 (PATRR22) as a translocation partner. Here, the constitutional rearrangement, t(3;8)(p14.2;q24.1), segregating with renal cell carcinoma in two families, is examined. The chromosome 8 breakpoint lies in PATRR8 in the first intron of the RNF139 (TRC8) gene while the chromosome 3 breakpoint is located in an AT-rich palindromic sequence in intron 3 of the FHIT gene (PATRR3). Thus, the t(3;8) is the first PATRR-mediated, recurrent, constitutional translocation that does not involve PATRR22. Furthermore, similar to the t(11;22) and t(8;22), we detect de novo translocations involving PATRR3 in normal sperm. The breakpoint on chromosome 3 is in proximity to FRA3B, the most common fragile site in the human genome and a site of frequent deletions in tumor cells. However, the lack of involvement of PATRR3 sequence in numerous FRA3B-related deletions suggests that there are several different DNA sequence based etiologies responsible for chromosome 3p14.2 genomic rearrangements.